Complementary processing of haptic information by slowly and rapidly adapting neurons in the trigeminothalamic pathway. Electrophysiology, mathematical modeling and simulations of vibrissae-related neurons - Sanchez-Jimenez, Abel; Torets, Carlos; Panetsos, Fivos (Frontiers in Cellular Neuroscience, 2013)
Tonic (slowly adapting) and phasic (rapidly adapting) primary afferents convey complementary aspects of haptic information to the central nervous system: object location and texture the former, shape the latter. Tonic and phasic neural responses are also recorded in all relay stations of the somatosensory pathway, yet it is unknown their role in both, information processing and information transmission to the cortex: we don’t know if tonic and phasic neurons process complementary aspects of haptic information and/or if these two types constitute two separate channels that convey complementary aspects of tactile information to the cortex. Here we propose to elucidate these two questions in the fast trigeminal pathway of the rat (PrV-VPM: principal trigeminal nucleus-ventroposteromedial thalamic nucleus). We analyze early and global behavior, latencies and stability of the responses of individual cells in PrV and medial lemniscus under 1-40 Hz stimulation of the whiskers in control and decorticated animals and we use stochastic spiking models and extensive simulations. Our results strongly suggest that in the first relay station of the somatosensory system (PrV): 1) tonic and phasic neurons process complementary aspects of whisker-related tactile information 2) tonic and phasic responses are not originated from two different types of neurons 3) the two responses are generated by the differential action of the somatosensory cortex on a unique type of PrV cell 4) tonic and phasic neurons do not belong to two different channels for the transmission of tactile information to the thalamus 5) trigeminothalamic transmission is exclusively performed by tonically firing neurons and 6) all aspects of haptic information are coded into low-pass, band-pass and high-pass filtering profiles of tonically firing neurons. Our results are important for both, basic research on neural circuits and information processing, and development of sensory neuroprostheses.